PENGARUH TEHNIK BERDZIKIR TERHADAP TINGKAT KEKAMBUHAN GANGGUAN PERSEPSI SENSORI HALUSINASI PENDENGARAN DI RSUD TOMBULILATO KECAMATAN BONE RAYA - Firmawati Firmawati; Sabirin B. Syukur (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
Increasing the popolation of mental disorders, making a variety of health problems and diseases that are typical in humans are increasing. The way to control the recurrence of sensory hallucinatory perception disturbances is by dhikr technique. Dhikr is the highest commemoration of prayer, in which there are various strengths and great benefits to our lives. The purpose of this study was to determine the effect of dzikir technique on recurrence rate in sensory auditory sensory perception patients at Tombulilato Bone Bolango Hospital, Gorontalo. This research design uses one group pretest postest research design that aims to reveal the cause of effect on one group of subjects that will be observed before the intervention and then re-observation after the intervention. The sample in this study were 22 patients of auditory hallucinations. The result of research shows that there is the effect of dzikir technique on the recurrence rate of sensory perception of auditory hallucinations in RSUD Tombulilato Subdistrict Bone Raya Bone Bolango District because P value = 0.000 (p <O, 005).